Banking patronage motives of the urban informal poor - Graham Saunders, Stephen; Bendixen, Mike; Abratt, Russell (The Journal of services marketing, 2007)
Purpose - The purpose of this paper is to provide an understanding of the banking needs of urban informal poor consumers in South Africa. These consumers find it difficult to obtain access to banking products.Design methodology approach - A survey of consumers was undertaken in a large informal settlement outside Johannesburg. A qualitative exploratory pilot study was undertaken first to gain a better understanding of these consumers and to develop a research instrument. Second, a quantitative analysis was undertaken among 200 households.Findings - Banking products used by the sample are discussed as well as all their patronage motives. It was established that the majority of consumers did have a bank account and there was a significant association between having an account and various demographics such as income level, employment status and level of education.Research limitations implications - Each informal settlement may have unique characteristics and therefore it may be difficult to generalize the findings.Practical implications - Banks will have to address the patronage factors of these consumers as they have very different needs when compared to middle and upper income customers. Specify strategies are recommended to bank management.Originality value - No study has been done on the banking needs of this segment of the market and very little is known about the urban informal poor in general. This paper gives insight into how banks can play their part in uplifting the poor in societies where they make up large segments of the population.